2015
DOI: 10.1136/annrheumdis-2015-207762
|View full text |Cite
|
Sign up to set email alerts
|

Gene copy-number variations (CNVs) of complementC4andC4Adeficiency in genetic risk and pathogenesis of juvenile dermatomyositis

Abstract: Objective Complement-mediated vasculopathy of muscle and skin are clinical features of juvenile dermatomyositis (JDM). We assess gene copy-number variations (CNVs) for complement C4 and its isotypes, C4A and C4B, in genetic risks and pathogenesis of JDM. Methods The study population included 105 JDM patients and 500 healthy European Americans. Gene copy-numbers (GCNs) for total C4, C4A, C4B and HLA-DRB1 genotypes were determined by Southern blots and PCRs. Processed activation product C4d bound to erythrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 54 publications
3
33
0
2
Order By: Relevance
“…Additionally, these potentially ‘high-risk’ individuals who were in the treatment group of the APPLE trial demonstrated slower CIMT progression over the course of the trial. We also noted an association between low C4A GCN and myositis, an observation which was consistent with our earlier report on C4A deficiency in juvenile dermatomyositis 38…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, these potentially ‘high-risk’ individuals who were in the treatment group of the APPLE trial demonstrated slower CIMT progression over the course of the trial. We also noted an association between low C4A GCN and myositis, an observation which was consistent with our earlier report on C4A deficiency in juvenile dermatomyositis 38…”
Section: Discussionsupporting
confidence: 93%
“…Specific HLA alleles are thought to target particular autoantigens, resulting in a breakdown in immunological tolerance to self-antigens. However, studies have shown that there are additional genetic features of the 8.1 AH that predispose individuals to immune-mediated diseases, such as NF-kappaB and TNF-alpha polymorphisms,18 19 and gene copy number variants of complement genes 20. The association of alleles independent of the 8.1 AH with anti-Mi-2 and anti-HMGCR, as well as finding that some autoantibodies do not have strong HLA associations, suggests that not all patients with IIM share a common genetic risk.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of C4A deficiency with the HLA risk allele DRB1*0301 in European Americans with SLE and the HLA allele DRB1*1501 in East Asians with SLE and other autoimmune diseases continues to be a fascinating topic in studies aimed at determining whether C4 CNVs or C4A deficiency and DRB1 genetic variants are independent, additive, or confounding disease risk factors . The pathologic effects of genetic and/or acquired deficiencies of C4, C1q, C1r, and C1s on SLE risk and pathogenesis have been found to be overwhelming .…”
Section: Discussionmentioning
confidence: 99%